Impact of complex medication regimens on adherence in multimorbidity senior citizen – Study from Nepal - Poonam Pant; Sudip Pandey; Santosh Khadka; Anju Joshi; Sajan Maharjan (PLoS ONE, 2026)
Background Elderly individuals often experience multiple comorbidities, requiring the use of several pharmacological therapies to improve their quality of life and extend life expectancy. However, medication non-adherence is a common issue in this population, potentially leading to significant clinical complications and increased healthcare costs. This study aims to evaluate medication regimen complexity and adherence among senior citizens in Nepal. Specifically, it explores factors associated with medication complexity and adherence, and examines the relationship between the two variables in the elderly population. Methods A cross-sectional descriptive study was conducted in selected wards of Chandragiri Municipality. Medication regimen complexity was assessed using the validated Medication Regimen Complexity Index (MRCI), while medication adherence was measured using Morisky Green Levine Adherence (MGLA) scale. Descriptive statistics (mean, standard deviation, frequency, and percentage) were used to summarize the data. Pearson’s chi-square test and correlation analysis were applied to examine the associations between MRCI levels and medication adherence. Ordinal logistic regression analysis was used to determine the impact of MRCI and other associated variables on adherence. A p-value <0.05 was considered statistically significant, and results were reported using adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results Out of 422 eligible participants, the majority of participants had a high MRCI score. A statistically significant association was found between MRCI and medication adherence (p < 0.05). Specific comorbidities, including diabetes mellitus, benign prostate hyperplasia (BPH), gastroesophageal reflux disease (GERD), thyroid disorder, chronic obstructive pulmonary disease (COPD), and coronary artery disease was significantly associated with increased MRCI scores. A weak positive correlation was observed between overall MRCI and adherence (r = 0.21), indicating a slight increase in adherence with increasing regimen complexity. Dosing frequency showed a strong correlation with MRCI (r = 0.92, p < 0.01) followed by total medication count, additional directions and dosage forms. In adjusted analysis, participants with higher MRCI level had significantly higher odds of non-adherence (AOR = 2.31, 95% CI: 1.03, 5.15). Additionally, individuals with ≥4 illnesses were more likely to be non-adherent (AOR = 3.82, 95% CI: 1.86–7.83) compared to those with two illnesses. Conclusion Most participants exhibited high medication regimen complexity, which negatively impacted adherence levels. These findings underscore the importance for healthcare providers to implement strategies aimed at simplifying medication regimens and supporting adherence, particularly among elderly individuals with multimorbidity.